2006
DOI: 10.2110/jsr.2006.020
|View full text |Cite
|
Sign up to set email alerts
|

Cambrian Depositional History of the Zanskar Valley Region of the Indian Himalaya: Tectonic Implications

Abstract: A well-preserved Cambrian section in the Zanskar Valley of northern India has previously been interpreted to record the transition from a passive to an active tectonic margin related to Cambrian-Ordovician orogenesis. This interpretation has been used to support the tectonostratigraphic interpretation of other successions across the Tethyan Himalaya. Our detailed paleoenvironmental analysis significantly revises the tectonic and depositional history of these Cambrian deposits: no definitive record of impending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 53 publications
2
84
0
Order By: Relevance
“…Wang et al (2010) and Yu et al (2007b) considered that the eastern SCB might be located at the northern margin of Gondwana linking Terra Australis orogen and Bhimphedian orogen during late early Paleozoic time. This link is also supported by (1) the similarity of detrital provenance and sedimentary sequences among the Northern India, Greater Himalaya, Lesser Himalaya and Cathaysia Blocks during late Neoproterozoic and early Paleozoic time (DeCelles et al, 2000;Gehrels et al, 2003;Myrow et al, 2006Myrow et al, , 2009Myrow et al, , 2010Metcalfe, 2011;Yu et al, 2007aYu et al, , 2007bWang et al, 2010), and (2) the unconformity between the Ordovician and Cambrian successions in northern India (e.g., Hughes, 2002;Myrow et al, 2009Myrow et al, , 2010, Hainan and Yunkai Domains of the eastern Cathaysia (e.g., Guangdong BGMR, 1988;Wang et al, 2010;Zhang AM et al, 2011). Thus we propose that the Kwangsian intracontinental orogeny of the Yangtze and Cathaysia Blocks might have geodynamically resulted from the far-field response for the amalgamation of the Australian-Indian plate and the Cathaysia (also Indochina) Block along the northern margin of east Gondwana.…”
Section: Tectonic Implicationsmentioning
confidence: 78%
“…Wang et al (2010) and Yu et al (2007b) considered that the eastern SCB might be located at the northern margin of Gondwana linking Terra Australis orogen and Bhimphedian orogen during late early Paleozoic time. This link is also supported by (1) the similarity of detrital provenance and sedimentary sequences among the Northern India, Greater Himalaya, Lesser Himalaya and Cathaysia Blocks during late Neoproterozoic and early Paleozoic time (DeCelles et al, 2000;Gehrels et al, 2003;Myrow et al, 2006Myrow et al, , 2009Myrow et al, , 2010Metcalfe, 2011;Yu et al, 2007aYu et al, , 2007bWang et al, 2010), and (2) the unconformity between the Ordovician and Cambrian successions in northern India (e.g., Hughes, 2002;Myrow et al, 2009Myrow et al, , 2010, Hainan and Yunkai Domains of the eastern Cathaysia (e.g., Guangdong BGMR, 1988;Wang et al, 2010;Zhang AM et al, 2011). Thus we propose that the Kwangsian intracontinental orogeny of the Yangtze and Cathaysia Blocks might have geodynamically resulted from the far-field response for the amalgamation of the Australian-Indian plate and the Cathaysia (also Indochina) Block along the northern margin of east Gondwana.…”
Section: Tectonic Implicationsmentioning
confidence: 78%
“…The final amalgamation along the Wuyi-Yunkai domain is roughly synchronous with the deformation of the East Ghats of India (∼960 Ma) and the northern Prince Charles Mountains of East Antarctica (∼990-960 Ma; e.g., Boger et al, 2000;Jayananda et al, 2000). These relationships, combined with the biogeographic consistency of the eastern SCB with Australia and the late Neoproterozoic tectonic relationship with India (e.g., Wang and Li, 2003;Yang et al, 2004;Myrow et al, 2006Myrow et al, , 2009Wang et al, 2010b), suggest to us that the SCB was situated along the margin of Rodinia between Australia and East Antarctica (e.g., Hoffman, 1991;Yang et al, 2004), as shown in Fig. 17.…”
Section: An Exterior Accretionary Orogen For the Scb Along The Marginmentioning
confidence: 93%
“…At ∼0.98-0.90 Ga (Fig. 18a), Eastern Cathaysia of the eastern SCB received orogenic detritus from the latest Mesoproterozoic mountain belt that lay in the Prince Charles mountains region of Antarctica (e.g., Myrow et al, 2006Myrow et al, , 2009Boger et al, 2000;Jayananda et al, 2000). At the same time, the Wuyi-Yunkai arc-back-arc system was developed and the Shuangxiwu system continued until ∼880 Ma.…”
Section: An Exterior Accretionary Orogen For the Scb Along The Marginmentioning
confidence: 99%
“…The proven Cambrian rocks in the Zanskar region are well exposed along a NW-SE trending outcrop belt, extending from Karsha village in the Padam Valley to the Niri-Tsarap Chu and Kurgiakh valleys (Fig.1). Stratigraphically, the Cambrian rocks of the Zanskar region are grouped under the Haimanta Group and are subdivided into the Phe, Parahio, Karsha and Kurgiakh formations (Nanda and Singh, 1977;Garzanti et al 1986;Gaetani et al 1986, Myrow et al 2006a). However, Srikantia et al (1978) (Myrow et al 2006a, b).…”
Section: Geological Setting and Stratigraphic Sectionmentioning
confidence: 99%
“…However, in the Zanskar region the lower boundary of the Parahio Formation is defined at the first appearance of trace fossils (Hughes and Droser, 1992) and the upper boundary is a conformable contact with the carbonates of the Thidsi Member of the Karsha Formation. Lithologically, the Parahio Formation consists of thin-to thickly-bedded shale, siltstone, sandstone and dolomite with episodically storm-influenced shoaling cycles deposited under offshore marine-shoreface to fluvial environments (Myrow et al 2006a). In the Zanskar region, body fossils have not been recorded from the lower part of the Parahio Formation, while the trace fossils are common in the sandy and muddy facies (Singh, 2008).…”
Section: Geological Setting and Stratigraphic Sectionmentioning
confidence: 99%